Fashion designer, creative authorship and revocation of a mark due to misleading use: Is anything acceptable to make the public believe that the designer still has a connection with the mark that corresponds to their surname? Commentary on the CJEU judgment of 18 December 2025 - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
The purpose of this paper is to examine the judgment of the CJEU of December 18, 2025, which resolved a preliminary question referred by the French Court of Cassation. The question posed by the national court to the CJEU is whether, under European trademark law, a trademark corresponding to the surname of its former owner (a well-known fashion designer in France) can be revoked because its current owner uses it in a way that attempts to mislead consumers into believing that the original owner remains associated with the trademark when this is not the case. This commentary will be divided into three parts. The first will address the facts of the case and its legal history; the second will briefly examine the lapse of a trademark under European law; and the final part will analyze and reflect upon the CJEU judgment of December 18, 2025.
Keywords: trade mark; fashion; misleading indication; consumer